Immune checkpoint inhibitor associated reactivation of primary membranous nephropathy responsive to rituximab. Issue 2 (5th October 2020) - Lin, Jamie S; Wang, Daniel Y; Mamlouk, Omar; Glass, William F; Abdelrahim, Maen; Yee, Cassian; Abudayyeh, Ala
Abstract : The same mechanisms that mediate antitumor immunity from checkpoint inhibitors (CPIs) can also lead to unintended targeting of normal tissues, characterized as immune-related adverse events (irAEs). Those with pre-existing autoimmune disease are believed to be particularly vulnerable for exacerbating underlying autoimmunity or inducing severe irAEs. We report the first case of CPI-associated reactivation of primary membranous nephropathy (MN) in a patient with pleural mesothelioma responding to immunotherapy. Due to its specificity in targeting B-lymphocytes, rituximab was used to treat primary MN with the expectation that this would not interfere with the benefits gained from T cell-mediated antitumor immunity. Rituximab was effective in treating CPI-associated reactivation of MN, and the patient was successfully rechallenged with nivolumab and maintained stable kidney function and sustained clinical antitumor effect. While exacerbation of pre-existing autoimmune diseases from CPIs is common, therapy for autoimmune reactivation can be rationally directed by an understanding of the immunosuppressive mechanism with goals of cancer treatment.